2021
DOI: 10.1002/anie.202101249
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized High Mannose‐Specific Lectins for the Discovery of Type I Mannosidase Inhibitors

Abstract: An engineered cyanovirin‐N homologue that exhibits specificity for high mannose N‐glycans has been constructed to aid type I α 1,2‐mannosidase inhibitor discovery and development. Engineering the lectins C‐terminus permitted facile functionalization with fluorophores via a sortase and click strategy. The resulting lectin constructs exhibit specificity for cells presenting high mannose N‐glycans. Importantly, these lectin constructs can also be applied to specifically assess changes in cell surface glycosylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 55 publications
(2 reference statements)
0
17
0
Order By: Relevance
“…To determine the ability of Cyt-CVNH to bind to high mannose presenting cancer cells, we utilized a fluorophore labelled Cyt-CVNH derivative (i. e., Cyt-CVNH MB 488) that we have previously described and applied in assays to demonstrate the presence of high mannose N-glycans on cells. [10] Here, Cyt-CVNH MB 488 was applied to assess the ability of Cyt-CVNH to bind to triple negative breast cancer (TNBC) MDA-MB-231 cells, lung adenocarcinoma A549 cells, and adenocarcinoma HT-29 cells, which have been previously described as high mannose presenting cancer cell lines by Matoba and co-workers. [9] Using flow cytometry, we observed that Cyt-CVNH MB 488 readily bound to MDA-MB-231, A549, and HT-29 cells (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine the ability of Cyt-CVNH to bind to high mannose presenting cancer cells, we utilized a fluorophore labelled Cyt-CVNH derivative (i. e., Cyt-CVNH MB 488) that we have previously described and applied in assays to demonstrate the presence of high mannose N-glycans on cells. [10] Here, Cyt-CVNH MB 488 was applied to assess the ability of Cyt-CVNH to bind to triple negative breast cancer (TNBC) MDA-MB-231 cells, lung adenocarcinoma A549 cells, and adenocarcinoma HT-29 cells, which have been previously described as high mannose presenting cancer cell lines by Matoba and co-workers. [9] Using flow cytometry, we observed that Cyt-CVNH MB 488 readily bound to MDA-MB-231, A549, and HT-29 cells (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…[19] To test this hypoth- ChemBioChem esis, we utilized TNBC MDA-MB-468 cells, as this cell line presents low levels of high mannose N-glycans, and the kifunensine analogue JDW-II-010 (5) to inhibit type I mannosidase (MAN I) enzymes. [10] When MDA-MB-468 cells were treated with 5 a significant increase in the binding of Cyt-CVNH MB 488 to the cells was observed by flow cytometry (Figure 4A), indicating that 5 increased the abundance of high mannose Nglycans. Next, we determined if treating MDA-MB-468 cells with 5 altered the sensitivity of these cells to Cyt-CVNH-GGG (4) and the LDCs 3 a and 3 b (Figure 4B-C).…”
Section: Chembiochemmentioning
confidence: 93%
See 2 more Smart Citations
“…NMR analysis allowed the characterization of the specific glycan epitopes recognized by each lectin, and paves the basis to unveil the roles played by glycosylation patterns in the interaction with receptors during infection. Another paper suggests that RBD can be put into relation with lectins, as a red-alga-derived lectin, griffithsin (GRFT), inhibits SARS-CoV-2 infection by targeting the glycosylation sites in the RBD of the SARS-CoV-2 S protein [ 23 , 24 ]. Although of interest, all these studies border their attention on the RBD of the S protein, despite the evidence that its extracellular portion is also constituted by the N-terminal domain ( Figure 1 —S1-NTD) encompassing residues 20–286.…”
Section: Introductionmentioning
confidence: 99%